Development of Non-Test Assessment Instrument Based on Genially Website Media For Global Warming Material - Yuliastrin, Adisti; Vebrianto, Rian; Yani, Deska Indri; Hardila, Dilva (Journal of Educational Science and Technology (EST), 2025)
. Existing non-test assessment instruments in science learning are often generic, less interactive, and insufficiently contextualized to address complex and socioscientific topics such as global warming. This limitation makes it difficult for teachers to assess students’ learning responses, engagement, and understanding in a meaningful way. Therefore, this study aims to develop and validate a Genially-based non-test assessment instrument specifically designed for global warming material, and to examine its feasibility as formative feedback to support instructional planning. This study employed a Research and Development (R&D) approach using the ADDIE model, which was selected due to its systematic and iterative structure that supports instructional product development and evaluation. The instrument was developed and tested on 30 respondents consisting of students and general users as initial users of the media, selected through random sampling for preliminary field testing. Data were collected using a questionnaire and analyzed to determine content validity, construct validity, reliability, and feasibility. The results indicate that all 19 instrument items are valid across five aspects: ease of use, presentation appeal, benefits, integration of Islamic values, and socio-scientific issues. The instrument demonstrated very high reliability, with a Cronbach’s alpha coefficient of 0.957. The feasibility analysis showed an average user response score of 76.45%, which falls into the “feasible” category, indicating that the instrument is appropriate for assessing learning media use in global warming instruction. This study contributes a validated, interactive non-test assessment instrument that can support teachers in conducting formative science assessment and evaluating students’ learning responses in global warming topics. Despite the limited sample size, the findings provide initial evidence of the instrument’s potential applicability and offer a foundation for further large-scale testing and refinement.